Adaptive Variation Amid High Gene Flow Across a Broad Latitudinal Gradient in the Reef‐Building Honeycomb Worm, Sabellaria alveolata - Edward J. Wilson; Antony M. Knights; Louise B. Firth; Charlotte Corporeau; Amelia Curd; Stanislas F. Dubois; Fernando P. Lima; Rui Seabra; Flavia L. D. Nunes (Molecular Ecology, 2026)
Climate change is already altering, and will continue to reshape, the persistence and spatial structure of marine populations. Understanding metapopulation connectivity and local adaptation is therefore critical for identifying both vulnerable populations and those with adaptive resilience. We applied a seascape genomics approach to investigate connectivity patterns and adaptive responses in the honeycomb worm, Sabellaria alveolata —an intertidal ecosystem engineer that supports high biodiversity and provides essential ecological functions. A total of 286 individuals from 17 sites spanning the entire latitudinal range were genotyped to assess population structure and local adaptation. Outlier analyses (BayeScan and OutFlank) identified six adaptive and 2117 neutral SNPs. Neutral SNP analysis revealed low to moderate genetic differentiation, indicating well‐connected populations. Admixture with possible ancestral gene pools in Southern Edge and Biscay populations suggests the persistence of unique genetic diversity. While connectivity is likely driven by natural larval dispersal, human‐mediated transport resulting from support vessels, aquaculture, marine debris and expanding offshore and coastal infrastructure may also facilitate gene flow, shaping observed genetic patterns. Despite this high connectivity, we detected genetic signatures of adaptation to temperature, salinity and net primary productivity, with adaptive SNPs linked to genes involved in molecular and physiological responses to these environmental factors. Our findings suggest that S. alveolata is likely resilient to climate change and other anthropogenic pressures, making it a valuable model for investigating the genetic and physiological underpinnings of marine population resilience.

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Linking persistent open-vent activity and caldera-forming eruptions at Tofua volcano, Tonga - Chris W. Firth; Shane J. Cronin; John T. Caulfield; Simon P. Turner; Adinda Peyra; James B. Garvin; Taaniela Kula; Annahlise Hall (Bulletin of Volcanology, 2026)
Tofua volcano (Tonga) currently exhibits persistent, open-vent activity; however, this contrasts with previous explosive, caldera-forming eruptions. To understand the relationship between these dichotomous eruption styles, we present new field observations and satellite remote sensing data that reveal excess degassing of SO 2 and demonstrate significant magma accumulation over timescales of centuries. Current activity takes the form of open-vent behaviour, with a small, active lava lake and persistent gas and heat emissions. Heat flux, determined by the Moderate Resolution Imaging Spectroradiometer, averages 6.9 MW and has been both persistent over 24 years and consistent in magnitude. SO 2 flux measured by in situ UV spectrometry in October 2022 averaged 8.1 kg/s. Satellite and aerial imagery reveal no change to the volcano’s morphology and negligible eruption of lava since at least 1968. Patchy historical reports suggest activity like this has continued for 200 years or more. The observed gas flux requires magma supply rates of 6.1 × 10 4 m 3 /day. These are clearly not matched by eruption rates, implying an excess degassing process with magma accumulating rapidly beneath the volcano. The history of this volcano suggests that such accumulated magma may be tapped on intervals as short as ~ 450 years to produce large-volume (5–10 km 3 ), caldera-forming eruptions. This is consistent with tephra records which show that two or possibly three large caldera-forming eruptions have occurred in the last 1.3 ka. This process is corroborated by 226 Ra isotope evidence, which shows that caldera-forming ignimbrites tapped magmas that were stored for 1–2 kyr longer than those feeding post-caldera lavas.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Could rear-arc volcanism be driven by mantle instability? - Alex C. Davidson; Chris W. Firth; Simon P. Turner; Shane J. Cronin (Chemical Geology, 2025)

Continent‐Wide Drivers of Spatial Synchrony in Breeding Demographic Structure Across Wild Great Tit Populations - Joe P. Woodman; Stefan J. G. Vriend; Frank Adriaensen; Elena Álvarez; Alexander Artemyev; Emilio Barba; Malcolm D. Burgess; Samuel P. Caro; Laure Cauchard; Anne Charmantier; Ella F. Cole; Niels Dingemanse; et al. (Ecology Letters, 2025)
Variation in age structure influences population dynamics, yet we have limited understanding of the spatial scale at which its fluctuations are synchronised between populations. Using 32 great tit populations, spanning 4° W–33° E and 35°–65° N involving > 130,000 birds across 67 years, we quantify spatial synchrony in breeding demographic structure (subadult vs. adult breeders) and its drivers. We show that larger clutch sizes, colder winters, and larger beech crops lead to younger populations. We report distance‐dependent synchrony of demographic structure, maintained at approximately 650 km. Despite covariation with demographic structure, we do not find evidence for environmental variables influencing the scale of synchrony, except for beech masting. We suggest that local ecological and density‐dependent dynamics impact how environmental variation interacts with demographic structure, influencing estimates of the environment's effect on synchrony. Our analyses demonstrate the operation of synchrony in demographic structure over large scales, with implications for age‐dependent demography in populations.

Magnetic resonance imaging shows spinal curvature in Chinook salmon ( Oncorhynchus tshawytscha ) is associated with chronic inflammation of peri‐vertebral soft tissues - Bailey A. Lovett; Elwyn C. Firth; Matthew R. Perrott; John S. Munday; Beau P. Pontre; Anna‐Maria P. Lydon; Jane E. Symonds; Mark A. Preece; Neill A. Herbert (Journal of Fish Diseases, 2024)
Chinook salmon ( Oncorhynchus tshawytscha ) farmed in New Zealand are known to develop abnormal spinal curvature late in seawater production. Its cause is presently unknown, but there is evidence to suggest a neuromuscular pathology. Using magnetic resonance imaging (MRI), we evaluated the relationship between soft tissue pathology and spinal curvature in farmed Chinook salmon. Regions of interest (ROIs) presenting as pathologic MRI signal hyper‐intensity were identified from scans of 24 harvest‐sized individuals: 13 with radiographically‐detectable spinal curvature and 11 without. ROIs were excised from individuals using anatomical landmarks as reference points and histologically analysed. Pathologic MRI signal was observed more frequently in individuals with radiographic curvature (92%, n = 12) than those without (18%, n = 2), was localized to the peri‐vertebral connective tissues and musculature, and presented as three forms: inflammation, fibrosis, or both. These pathologies are consistent with a chronic inflammatory process, such as that observed during recovery from a soft tissue injury, and suggest spinal curvature in farmed Chinook salmon may be associated with damage to and/or compromised integrity of the peri‐vertebral soft tissues. Future research to ascertain the contributing factors is required.

A multinational survey of companion animal veterinary clinicians: How can antimicrobial stewardship guidelines be optimised for the target stakeholder? - S. Farrell; A.F. Bagcigil; S.C. Chaintoutis; C. Firth; F.G. Aydin; C. Hare; M. Maaland; A. Mateus; A.P. Vale; U. Windahl; P. Damborg; D. Timofte; et al. (The Veterinary Journal, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Taking sides? Aspect has limited influence on soil environment or litter decomposition in pan-European study of roadside verges - A. Amstutz; LB. Firth; JI. Spicer; P. De Frenne; L. Gómez-Aparicio; BJ. Graae; S. Kuś; S. Lindmo; A. Orczewska; F. Rodríguez-Sánchez; P. Vangansbeke; T. Vanneste; et al. (Pedobiologia, 2024)

Applying landscape metrics to species distribution model predictions to characterize internal range structure and associated changes - Amelia Curd; Mathieu Chevalier; Mickaël Vasquez; Aurélien Boyé; Louise B. Firth; Martin P. Marzloff; Lucy M. Bricheno; Michael T. Burrows; Laura E. Bush; Céline Cordier; Andrew J. Davies; J. A. Mattias Green; et al. (Global Change Biology, 2023)
Distributional shifts in species ranges provide critical evidence of ecological responses to climate change. Assessments of climate‐driven changes typically focus on broad‐scale range shifts (e.g. poleward or upward), with ecological consequences at regional and local scales commonly overlooked. While these changes are informative for species presenting continuous geographic ranges, many species have discontinuous distributions—both natural (e.g. mountain or coastal species) or human‐induced (e.g. species inhabiting fragmented landscapes)—where within‐range changes can be significant. Here, we use an ecosystem engineer species ( Sabellaria alveolata ) with a naturally fragmented distribution as a case study to assess climate‐driven changes in within‐range occupancy across its entire global distribution. To this end, we applied landscape ecology metrics to outputs from species distribution modelling (SDM) in a novel unified framework. SDM predicted a 27.5% overall increase in the area of potentially suitable habitat under RCP 4.5 by 2050, which taken in isolation would have led to the classification of the species as a climate change winner. SDM further revealed that the latitudinal range is predicted to shrink because of decreased habitat suitability in the equatorward part of the range, not compensated by a poleward expansion. The use of landscape ecology metrics provided additional insights by identifying regions that are predicted to become increasingly fragmented in the future, potentially increasing extirpation risk by jeopardising metapopulation dynamics. This increased range fragmentation could have dramatic consequences for ecosystem structure and functioning. Importantly, the proposed framework—which brings together SDM and landscape metrics—can be widely used to study currently overlooked climate‐driven changes in species internal range structure, without requiring detailed empirical knowledge of the modelled species. This approach represents an important advancement beyond predictive envelope approaches and could reveal itself as paramount for managers whose spatial scale of action usually ranges from local to regional.

Who to help? Helping decisions in a cooperatively breeding bird with redirected care - Nicole J. Sturrock; Ben J. Hatchwell; Josh A. Firth; Jonathan P. Green (Behavioral Ecology and Sociobiology, 2022)
Cooperative breeding sometimes occurs when adult breeders form groups following natal dispersal and mating. In such cases, individuals typically face a choice of social partner with whom to cooperate. Selecting appropriate social partners is crucial to maximising the fitness payoffs from cooperation, but our understanding of the criteria guiding partner choice is limited. Here, we analyse helping decisions by long-tailed tits ( Aegithalos caudatus ), which may redirect their care to assist breeders in raising offspring following the failure of their own nests. In this species, helpers prefer to help relatives at nearby nests, but it is unclear whether other criteria that may affect helper fitness also influence helping decisions. When choosing among broods of equivalent kinship, we found that helpers did not prefer those broods that offered the greatest indirect fitness returns. Further analyses revealed that helpers did not choose nests on the basis of brood size or age, but were more likely to help broods that were closer to their own failed nests and that were already being cared for by other helpers. Both effects likely reflect the limited choice available to helpers: although individuals breed close to relatives within kin neighbourhoods, a high rate of nest predation constrains helpers’ choice of broods. In other species where cooperatively breeding groups form after natal dispersal, a greater range of options may be available and here detailed analysis of group formation will be helpful for determining the decision rules that underpin partner choice and permit stable cooperation in the face of alternative options. Significance statement Cooperative breeding occurs most frequently when offspring delay dispersal from their natal site and help to care for their younger siblings. In some species, however, individuals first disperse and then come together as adults to cooperate in rearing young. In the latter case, multiple social partners may be available — what then determines which partner is helped? We studied partner choice in long-tailed tits, which may help to feed other broods if their own brood fails. When multiple related broods were available, individuals were more likely to help those close by but showed no preference for broods offering the greatest indirect fitness returns. One explanation for this result is that helping options for most individuals are limited by high levels of nest predation, favouring a simpler decision-making process based on identifying close relatives breeding in close proximity.

Drivers of passive leadership in wild songbirds: species-level differences and spatio-temporally dependent intraspecific effects - Samin Gokcekus; Josh A. Firth; Charlotte Regan; Ella F. Cole; Koosje P. Lamers; Ben C. Sheldon (Behavioral Ecology and Sociobiology, 2021)
Collective behaviors are typical for many social species and can have fitness benefits for participating individuals. To maximize the benefits obtained from group living, individuals must coordinate their behaviors to some extent. What are the mechanisms that make certain individuals more likely to initiate collective behaviors, for example, by taking a risk to initially access a resource (i.e., to act as “leaders”)? Here, we examine leading behavior in a natural population of great tits and blue tits. We use automated feeding stations to monitor the feeder visits of tagged individuals within mixed-species flocks, with a small cost (waiting Significance statement Many species are social and engage in collective behaviors. To benefit from group actions, individuals need to fulfill different roles. Here, we examine leading behavior during feeding events; who feeds first when birds arrive at a resource? In mixed-species flocks of passerines, great tits (the larger and more dominant species), males, and individuals with higher levels of activity lead more often than blue tits, females, and individuals with lower levels of activity. While the species effect remains even when we control for the locations and dates of individual feeder visits, the effects of sex and activity are dependent on when and where birds choose to feed.

Musical Chairs on Temperate Reefs: Species Turnover and Replacement Within Functional Groups Explain Regional Diversity Variation in Assemblages Associated With Honeycomb Worms - Alexandre Muller; Camille Poitrimol; Flávia L. D. Nunes; Aurélien Boyé; Amelia Curd; Nicolas Desroy; Louise B. Firth; Laura Bush; Andrew J. Davies; Fernando P. Lima; Martin P. Marzloff; Claudia Meneghesso; et al. (Frontiers in Marine Science, 2021)
Reef-building species are recognized as having an important ecological role and as generally enhancing the diversity of benthic organisms in marine habitats. However, although these ecosystem engineers have a facilitating role for some species, they may exclude or compete with others. The honeycomb worm Sabellaria alveolata ( Linnaeus, 1767 ) is an important foundation species, commonly found from northwest Ireland to northern Mauritania, whose reef structures increase the physical complexity of the marine benthos, supporting high levels of biodiversity. Local patterns and regional differences in taxonomic and functional diversity were examined in honeycomb worm reefs from 10 sites along the northeastern Atlantic to explore variation in diversity across biogeographic regions and the potential effects of environmental drivers. While taxonomic composition varied across the study sites, levels of diversity remained relatively constant along the European coast. Assemblages showed high levels of species turnover compared to differences in richness, which varied primarily in response to sea surface temperatures and sediment content, the latter suggesting that local characteristics of the reef had a greater effect on community composition than the density of the engineering species. In contrast, the functional composition of assemblages was similar regardless of taxonomic composition or biogeography, with five functional groups being observed in all sites and only small differences in abundance in these groups being detected. Functional groups represented primarily filter-feeders and deposit-feeders, with the notable absence of herbivores, indicating that the reefs may act as biological filters for some species from the local pool of organisms. Redundancy was observed within functional groups that may indicate that honeycomb worm reefs can offer similar niche properties to its associated assemblages across varying environmental conditions. These results highlight the advantages of comparing taxonomic and functional metrics, which allow identification of a number of ecological processes that structure marine communities.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Constraints on the development of orogenic style gold mineralisation at Mineral de Talca, Coastal Range, central Chile: evidence from a combined structural, mineralogical, S and Pb isotope and geochronological study - Emily A. Firth; David A. Holwell; Nicholas H. S. Oliver; James K. Mortensen; Matthew P. Rovardi; Adrian J. Boyce (Mineralium Deposita, 2015)

Protecting asset value and driving performance with a dynamic, risk-based contingency fund - C. W. Mauelshagen; S. J. T. Pollard; D. Owen; S. Herndlhofer; P. Firth; J. McKenna; N. Bingley; P. Jenson (Environment Systems and Decisions, 2014)

The eruptive history and chemical stratigraphy of a post-caldera, steady-state volcano: Yasur, Vanuatu - Chris W. Firth; Heather K. Handley; Shane J. Cronin; Simon P. Turner (Bulletin of Volcanology, 2014)

Recurrent Emergence of Catalytically Inactive Ornithine Decarboxylase Homologous Forms That Likely Have Regulatory Function - Ivaylo P. Ivanov; Andrew E. Firth; John F. Atkins (Journal of Molecular Evolution, 2010)

Competition and habitat suitability: small-scale segregation underpins large-scale coexistence of key species on temperate rocky shores - Louise Bridget Firth; Tasman P. Crowe (Oecologia, 2010)

Predicting impacts of climate‐induced range expansion: an experimental framework and a test involving key grazers on temperate rocky shores - LOUISE B. FIRTH; TASMAN P. CROWE; PIPPA MOORE; RICHARD C. THOMPSON; STEPHEN J. HAWKINS (Global Change Biology, 2009)
Climate change has strong potential to modify the structure and functioning of ecosystems, but experimental field studies into its effects are rare. On rocky shores, grazing limpets strongly affect ecosystem structure and their distribution in NW Europe is changing in response to climate change. Three limpet species co‐occur in SW Britain ( Patella vulgata, Patella ulyssiponensis and Patella depressa ) on open rock and in pools. Shores in Ireland are similar, but currently lack P. depressa . It is anticipated that P. depressa will expand its range into Ireland as the climate warms, but we currently lack an empirical basis to predict the consequences of this change. Recent studies show that increasing abundance of P. depressa on British shores has been accompanied by a decline of P. vulgata suggesting interspecific competition. In this study, a new experimental framework was used to examine the potential for P. depressa to affect P. vulgata on Irish shores. P. vulgata was experimentally transplanted into enclosures on open rock and in pools in both Ireland and Britain. In pools, treatments also included transplanted P. ulyssiponensis to mimic natural assemblages. Growth and mortality of P. vulgata were measured over 6 months with no differences between Ireland and Britain. In Britain, P. vulgata caged in pools with transplanted P. depressa and P. ulyssiponensis showed reduced growth, compared with when caged in pools with P. ulyssiponensis alone. There was no effect of P. depressa on the growth rate of P. vulgata on open rock. Results indicate that if the range of P. depressa extends into Ireland, it would reduce the growth of P. vulgata where it co‐occurs with P. ulyssiponensis in pools. The framework used here provides a field‐based approach that could be used to examine the impacts of climate‐induced range expansions on the structure and functioning of other ecosystems.

Large-scale coexistence and small-scale segregation of key species on rocky shores - Louise B. Firth; Tasman P. Crowe (Hydrobiologia, 2008)

Molecular analysis of eight mutations in FBN1 - D. Halliday; S. Hutchinson; S. Kettle; P. A. Handford; H. Firth; P. Wordsworth (Human Genetics, 1999)

Molecular analysis of eight mutations in FBN1 - D. Halliday; S. Hutchinson; S. Kettle; H. Firth; P. Wordsworth; P. A. Handford (Human Genetics, 1999)